Analysis of solar underfloor heating system assisted with nano enhanced phase change material for nearly zero energy buildings approach - Gur, Muhammed; Öztop, Hakan Fehmi; Selimefendigil, Fatih (Pergamon-Elsevier Science Ltd, 2023)
This study focuses on the design of a solar-assisted underfloor heating system specifically tailored for nearly zeroenergy buildings. The system incorporates a Photovoltaic/Thermal (PV/T) collector as the primary heat source. The analysis takes into account the geographical coordinates of Elazig province in Turkey, and the boundary conditions are carefully chosen as the inlet parameters in the program. To enhance the system's performance, Nano-enhanced Phase Change Material (PCM) is utilized by filling pockets around the underfloor heating pipe with varying thicknesses. Cu nanoparticles of 1% solid volume fraction is considered. The fundamental objective of this approach is to achieve room temperature without any additional energy consumption during nighttime periods when solar radiation is unavailable. To investigate the impact of the system, copper nanoparticles are introduced to the PCM, and their effects on room temperature are numerically analyzed using the finite volume method under turbulent flow conditions. Realistic building conditions are considered, and a container is selected as the scenario building for simulations. The results reveal that the best room temperature conditions are obtained with pure PCM of width k (Case 1), pure PCM of width k/2 (Case 3), PCM with nanoparticle added of width k/2 (Case 3), and no PCM (Case 4), respectively. The highest temperature difference of 4 K is obtained between the configurations of Case 1 and Case 4 which shows the favorable impacts of using PCM. However, between the cases of using nano-PCM and PCM, room temperature difference of 0.1 K is obtained which indicates the very slight improvement of using nano-powders in PCM for this energy system. These findings provide valuable insights into the design and optimization of solar-assisted underfloor heating systems for nearly zeroenergy buildings, offering the potential to improve energy efficiency and thermal comfort.
Keywords: Solar energy; Underfloor heating system; Nearly zero energy buildings; Nanoenhanced phase change material; Computational fluid dynamics